The linguistic landscape of Paris’s 2024 Marche des fiertés LGBTQ+ - Eilderts, Luke L. (Contemporary French Civilization, 2026)
This article examines the linguistic landscape of Paris’s 2024 Marche des fiertés LGBTQ+ through an analysis of 122 participant-produced signs. Drawing on linguistic landscape theory, it explores how language choice shapes political, social, and cultural expression in this highly visible public event. The findings show that language use is structured rather than random. French predominates in signs expressing political critique, satire, and wordplay, positioning it as the primary medium for engaging domestic audiences, particularly in the context of the 2024 legislative elections. English, by contrast, is frequently used for messages of solidarity, identity affirmation, and pop-cultural reference, aligning with transnational activist discourse. Multilingual signs often bridge these functions. The article argues that this distribution reflects the strategic deployment of language to address distinct yet overlapping publics, demonstrating how Pride participants use written language to negotiate identity, politics, and belonging in contemporary France.This article was published open access under a CC BY-NC-ND licence: https://creativecommons.org/licenses/by-nc-nd/4.0/.
Keywords: dept.wll

Adding the Content Back in: Technology-Assisted PBLL across the FL Curriculum - Gleason, Jesse (Project-Based Learning in Language and Content Teacher Education, 2026)
In response to a call for PBLL to address language learners’ 21st-century needs, the present chapter showcases two examples of technology-assisted PBLL (TAPBLL) carried out in 100- and 300-level Spanish courses at a regional public university in the eastern United States. The TAPBLL using Generative AI chatbots in the lower-division Spanish course exemplified how content could be foregrounded in foreign language (FL) courses that might otherwise tend to overemphasize grammar. The TAPBLL using collaborative online international learning as a virtual exchange project in an (or the) upper-division course exemplifies how content can be prioritized early and often through projects that address learners’ 21st-century needs. When woven throughout the FL curriculum, TAPBLL can successfully build learners’ bilingualism, digital literacies, and cultural competence while at the same time working to counteract decreasing FL enrollments and imprudent narratives concerning the inapplicability of FL instruction to learners’ future academic and career goals.
Keywords: dept.wll

La Colonia Digital Archive: New Haven's Italian American Community, 1890–1930 - Larkin, Erin (2026)
La Colonia Digital Archive: New Haven's Italian American Community, 1890–1930 is an open-access digital humanities project documenting the professional and civic life of New Haven's Italian American community between 1890 and 1930. The archive is based on Antonio Cannelli's La Colonia Italiana di New Haven (1921), a 373-page Italian-language volume combining a community Who's Who with a survival guide for new immigrants. Cannelli documented 248 individuals and more than 90 businesses, including physicians, attorneys, pharmacists, musicians, grocers, and bankers. Cannelli published his volume in 1921, the same year that Nicola Sacco and Bartolomeo Vanzetti went on trial for murder in Massachusetts; they were convicted on July 14, 1921, and sentenced to death in a case that became an international cause célèbre and a defining watershed of anti-immigrant sentiment directed specifically at Italians. The trial unfolded against a broader landscape of systematic exclusion: the Emergency Quota Act of 1921 had passed just months earlier, sharply restricting Southern and Eastern European immigration, and Italians faced sustained targeting, marginalization, and persistent characterization as unskilled, unassimilable, and threatening. Cannelli's documentation was deliberate advocacy in precisely this climate: a counter-narrative assembled to demonstrate the professional achievement, civic engagement, and cultural diversity and richness of a community that dominant American discourse refused to acknowledge. La Colonia Digital Archive makes that narrative searchable and accessible to researchers, descendants, and the general public, plotting archival documents and photographs onto contemporary maps of New Haven and the surrounding area. The archive is currently in active pre-launch development. Public release is planned for 2026, with ArcGIS StoryMap components to be added through 2026–2027.
Keywords: Cultural heritage; Digital Archives; Diversity (politics); Documentation; Haven; Narrative; dept.wll

Review of: "Why Native Language Secrecy No Longer Works in Modern Warfare: The Case of North Koreans in the Russo-Ukrainian War" - Sorokina, Anastasia (Qeios, 2025)
Keywords: Ancient history; Geography; History; Law; Linguistics; Philosophy; Political science; Secrecy; Ukrainian; dept.wll

Turning to returnees - Schmitt, Elena (Linguistic Approaches to Bilingualism, 2025)
Keywords: dept.wll

Humanistic Education: A Collection of Reflective Essays - Narvaez, George (Independently published, 2025)
Humanistic Education: A Collection of Reflective Essays by George Narvaez is a compelling anthology that bridges classical philosophy, modern educational theory, and personal reflection. Drawing on the author’s graduate studies at Harrison Middleton University, these twenty essays offer a deep dive into the evolution of human thought on education, knowledge, and the art of learning.This book is ideal for readers interested in the humanities, education, philosophy, or self-directed learning. It engages with timeless questions:What does it mean to “know” something?How is knowledge constructed and communicated?How can education empower individuals and communities?Inside this collection, you will explore:✔️ The foundational philosophies of Plato, Aristotle, Augustine, and Aquinas✔️ Modern insights from William James, John Dewey, and Benjamin Franklin✔️ The evolution of rhetoric and epistemology across history✔️ The relationship between language, culture, and cognition✔️ The author's transformative journey through educationEach essay combines academic rigor with accessible language, offering readers a path to understand how classical theories of liberal education connect with contemporary learning practices. From the “education of the hemispheres” in William James’s psychology to the experiential learning of Franklin and Dewey, the author shows that learning is not just about absorbing information—it’s about transforming the way we live, communicate, and understand ourselves and others.Key themes include:Rhetoric as a tool for empowermentEpistemology as a process of inquiryCivic responsibility through educationPersonal growth through humanistic reflectionWhether you're an educator, student, scholar, or lifelong learner, Humanistic Education is a thought-provoking guide to the intellectual traditions that continue to shape our educational ideals.Start your journey through the minds of history’s greatest thinkers—and reflect on your own learning path.

Bilingual autobiographical memory: unveiling the significance of memories encoded in multiple languages - Sorokina, Anastasia (Multilingua, 2025)
Keywords: Autobiographical memory; Cognitive psychology; Cognitive science; Computer science; Linguistics; Philosophy; Psychology; Recall; bilingual autobiographical memory; dept.wll; memory phenomenology; mixed memories; peer-reviewed

“It’s where she belongs, isn’t it?” Lupe Vélez and Dolores del Río in Hollywood - Hernández-Rodríguez, R. (Nomadic New Women: Exile and Border-Crossing between Spain and the Americas, Early to Mid-Twentieth Century, 2024)
Mexican artistic influence at the beginning of the twentieth century was prevalent in America, most notably muralism, but also talent associated with the movies. This influenced the way Mexico was perceived in the United States, and by extension the way Lupe Vélez and Dolores del Río, the most successful Mexican actresses in early Hollywood, were appreciated. Both actresses had come to Hollywood to fulfill their dream of a career in the movies. At first, they were successful playing a variety of roles in silent movies, but once sound arrived, their accents made obvious their foreignness at a time when American culture was beginning to spread around the world and to establish its preeminence. They were aware of the challenges they faced and knew there was a price to pay if they wanted to continue in a business where the public decided, at a time when Americans distrusted foreigners. So, if that price was to overplay her earthy Mexicaness, in the case of Vélez, or emphasize her aristocratic image, in the case of del Río, they were ready to pay it. Mexico became the other par excellence in the early twentieth century, and these heavily accented actresses were evidence of that.
Keywords: Dolores del Río; Ethnic representation; Hollywood; Identity; Lupe Vélez; Mexican influence; Silent films; Stereotypes; Talkies; dept.wll

Reducing opportunity gaps and promoting enrollment through credit by examination for the Seal of Biliteracy - Gleason, Jesse; Latorre, Sobeira; Cardone, Resha (The Seal of Biliteracy in Higher Education, 2024)
This chapter explores the impact of implementing a partnership agreement to grant incoming university students credit based on their documented language proficiency. In 2018, an agreement was forged between an urban university and public school district, and, by extension, any high school offering the Seal of Biliteracy (SoBL) to offer students who hold the SoBL university credit for their language proficiency in a world language. This chapter examines the evolution of that agreement over a five-year period and its potential impact on students’ decision to pursue a minor/major in Spanish. Through semi-structured interviews, we also examined multiple university stakeholders’ perceptions and/or experiences about the value of the SoBL, the agreement to grant credit by examination (CBE), as well as other challenges, including the university’s reduction of their language requirement, transitions in leadership, and differing ideas about if and how best to award students credit based on examination.
Keywords: dept.wll

First language loss effect on bilingual autobiographical memory: examining memory phenomenology - Sorokina, A.N. (Applied Linguistics Review, 2024)
In the context of globalization and migration, individuals may experience language loss or first language (L1) attrition. While migrant language loss is well documented and researched, its impact on bilingual autobiographical memory remains underexplored. Existing research indicates that bilingual speakers encode memories in either their L1 or second language (L2), depending on the language context of the event. Language’s pivotal role in autobiographical memory has also been confirmed by bilingual psychotherapy research. This paper investigates whether L1 attrition can impair memories encoded in that language. Focusing on Russian-English speakers with various degrees of L1 attrition, this study examines the phenomenological characteristics of memories (vividness, emotional valence, accessibility, significance, and confidence in the event). Results from partial correlation and linear regression analyses demonstrated that language loss significantly compromises vividness and confidence, underscoring language’s integral function in maintaining bilingual autobiographical memory. © 2024 De Gruyter Mouton. All rights reserved.
Keywords: L1 attrition; bilingual autobiographical memory; dept.wll; memory phenomenology; peer-reviewed

Margherita Marchione as Antihero for Italian Jews: A Complex Message of Hope - Vitale, L. (A Century of Italian War Narratives: Voices from the Sidelines, 2023)
Lisa Vitale discusses the intellectual contribution of historian and apologist Margherita Marchione in redefining the role of Pius XII during the atrocities of the Nazi Holocaust by means of personal narratives of the Sisters of St Lucy Filippini (of which Marchione was a member) and the Jewish refugees they sheltered, including the prominent Roman Di Veroli family. The chapter paints a multi-faceted, and sometimes contradictory, picture of Catholic charity during those turbulent and confusing times. Despite Marchione’s defense of Vatican (in-)action during the mass extermination of the Jews, she brings a message of hope to today’s Jewish Italian citizens. © 2023 by Koninklijke Brill NV, Leiden, The Netherlands.
Keywords: dept.wll

Partisan Diary: Ada’s Wars - Palma, P. (A Century of Italian War Narratives: Voices from the Sidelines, 2023)
This chapter focuses on the figure of Ada Gobetti and her humble, yet crucial contribution, as a partisan collaborator and leader who helped dismantle the Nazi-Fascist political system in the aftermath of the 1943 Armistice. The author aims at shedding new light on Gobetti’s work that has long been ignored, highlighting how women regained visibility because of their role in support of the Resistance. © 2023 by Koninklijke Brill NV, Leiden, The Netherlands.
Keywords: dept.wll

Challenges and achievements of an online intercultural exchange in time of crisis - Fornara, F; Gleason, Jesse (How We Take Action: Social Justice in PK-16 Language Classrooms, 2023)
How We Take Action brings together practical examples of social justice in language education from a wide range of contexts. Many language teachers have a desire to teach in justice-oriented ways, but perhaps also feel frustration at how hard it is to teach in ways that we did not experience ourselves as learners and have not observed as colleagues. As a profession, we need more ideas, more examples, and wider networks of allies in this work. This book includes the work of 59 different authors including teachers and researchers at every level from Pre-K to postsecondary, representing different backgrounds, languages, and approaches to classroom practice. Organized into three sections, some of the chapters in this collection report on classroom research while others focus on key practices and experiences. Section I is entitled Inclusive and Empowering Classrooms. In this section authors take a critical approach to classroom practices by breaking with the status quo or creating spaces where students experience safety, access, and empowerment in language learning experiences. Section II, Integration of Critical Topics, addresses a variety of ways teachers can incorporate justice-oriented pedagogies in day-to-day instructional experiences. Social justice does not happen haphazardly; it requires careful, critical examination of instructional practices and intentional planning as instructors hope to enact change. Section III, Activism and Community Engagement, explores how teachers can empower students to become agents for positive change through the study of activism and constructive community engagement programs at local and global levels.
Keywords: dept.wll

Guest editorial: Language attrition – a comprehensive introduction - Schmitt, Elena; Sorokina, Anastasia (The Language Learning Journal, 2024)
Keywords: dept.wll

Embracing bilingualism: L1 retention amidst L2 acquisition - Sorokina, A.; Mugno, R. (Language Learning Journal, 2024)
In L1 attrition research, it's recognized that a previously acquired language can transform under the influence of a newly acquired one. However, the precise L1-L2 relationship is intricate and warrants further study. Some research suggest that L2 mastery might reduce L1 proficiency, while others show that both languages can be maintained. Age of onset and L1 use are the factors that have been discussed in the debate surrounding L1 attrition. The study aims to contribute to the ongoing discussion by examining L1 and L2 proficiency of Russian-English bilingual speakers (N = 35). The participants with comparable L2 proficiency but various degrees of L1 attrition who arrived at different ages and differed in their frequency of L1 use were recruited for the study. This diverse group provided an ideal quality sample for investigating the role of age of onset and L1 use, as well as the interplay between L1 and L2. By comparing L1 and L2 lexical diversity, syntactic complexity, and fluency, the study revealed that higher L2 proficiency was not associated with lower levels of L1 proficiency, suggesting that L1 retention is possible amidst L2 acquisition. L1 use played a more significant role in the L1 maintenance of these bilingual individuals. © 2024 Association for Language Learning.
Keywords: L1 attrition; L1 maintenance; L1 use; age of onset; bilingualism; dept.mat; dept.wll; peer-reviewed

A Century of Italian War Narratives: Voices from the Sidelines - Gussago, Luigi; Palma, Pina (Brill, 2023)
Keywords: Contemporary History; Criticism & Theory; Cultural History; History; Literary Relations; Literature and Cultural Studies; Memory Studies; dept.wll

A case study on the role of project-based learning in improving university students’ speaking skills: From theory to practice - Trihn, Nguyen Thi Tu; Schmitt, Elena (Konińskie Studia Językowe, 2020)
The aims of this paper are twofold: (1) to study the application of project-based learning ten-step process framework suggested by Alan and Stoller (2005) to boost English speaking ability of undergraduate students at the University of Da Nang, and (2) to investigate the levels of undergraduate students’ satisfaction. The subjects were 24 final year undergraduate engineering students at the university of Da Nang during the first semester of the 2019/2020 academic year. The instruments used in this experiment included lesson plans, a project evaluation form, a student’s self-assessment form, a satisfaction questionnaire and interviews
Keywords: English speaking skills; dept.wll; peer-reviewed; project-based learning; self-assessment

The knowledge framework for building teacher awareness of language in content instruction - Schmitt, Elena; Gleason, Jesse (Social Practices in Higher Education; A Knowledge Framework Approach to Linguistic Research and Teaching; Slater, 2023)
Keywords: dept.wll

Bilingualism - Schmitt, Elena G. (Encyclopedia of Slavic Languages and Linguistics Online, 2023)
Keywords: dept.wll

Ecocritical Reflections on Fiction Written by Nobel Laureate Mario Vargas Llosa - Flores, W. (Humanidades, 2023)
This article examines anthropocentric and ecocentric tendencies in two major works written by Mario Vargas Llosa, The Storyteller and The Dream of the Celt, to identify the value of those novels in ecocritical terms. I provide this analysis in the context of recent academic dialogue which notes an apparent contradictory relationship between the presentation of abuses of Amazonian people and their environment, and the portrayal of Westernized protagonists as their saviors in fiction written by Vargas Llosa. This essay provides a solution to this paradox and other apparent contradictions in his narratives and posits that even though the anthropocentric literary discourse concerning the environment has declined throughout the latter part of the twentieth century, in part, due to the rise of the environmental movement, this type of discourse has changed in Vargas Llosa’s literature, rejecting early twentieth century misconceptions of the natural world but holding onto technocentric neoliberal beliefs. © 2023, University of Montevideo. All rights reserved.
Keywords: Mario Vargas Llosa; Peruvian literature; The Dream of the Celt; The Storyteller; dept.wll; ecocriticism; environment; peer-reviewed

Saciar el hambre y la retina: alimentos, identidad y ambivalencia nacional en López Velarde - Hernandez, Rafael (Tema y Variaciones de Literatura, 2021)
Keywords: dept.wll; ⛔ No DOI found

Melodrama y mitología: imágenes de la migración en Guten Tag, Ramón y Señales que precederán al fin del mundo” - Hernandez, Rafael (Hispanos en el mundo. Emociones y desplazamientos históricos, viajes y migraciones, 2021)
Keywords: dept.wll

The Dark Night of Mexico: Picaresque, Sexuality, and Violence in El vampiro de la colonia Roma and Las púberes canéforas - Hernandez, Rafael (Growing Up in Latin America. Child and Youth Agency in Contemporary Popular Culture., 2022)
Keywords: dept.wll

Hospitality and Power: Pontano’s Book Virtues - Palma, Pina (Early Modern Cultures of Hospitality, 2021)
Keywords: dept.wll

Of Cranes, Dinners, and Desire: Decameron VI, 4 - Palma, Pina (Italica, 2021)
Through the analysis of a hosted dinner, crane-meat, its preparation, and a lover's ultimatum the article shows that in Chichibio's novella (Decameron VI,4) there is more at play than just the lies, wit, and cunning that a Venetian cook relies on as survival mode. In fact, the roasted crane-leg stolen by the cook for his lover upends the established social and cultural order that Currado Gianfigliazzi exemplifies. Pruning away at established norms while depicting a servant who projects self-confidence, shrewdness, and the ability to adjust to contingencies, Boccaccio's tale demonstrates that Chichibio's (and his lover's) personal fulfillment rests neither on prides nor privileges, but on their ability to envision and seize what lies beyond the norms.
Keywords: Boccaccio; Bouchard, Norma; Congregational churches; Currado Chichibio; Dialects; Epilepsy; Hunting; crane; dept.wll; food; hunting; kitchen; master; power and powerlessness; servant; ⛔ No DOI found

For His Wife and Lover: Pontano's De amore coniugali - Palma, Pina (Idealizing Women in the Italian Renaissance, 2022)
Keywords: dept.wll

全球视野中的海外华人和中华文化 [Chinese Diasporas and Traditional Culture in the Global Context] - Weng, Miaowei (《中国与拉美》 [China and Latin America], 2022)
Keywords: dept.wll; peer-reviewed; ⛔ No DOI found

美洲华人简史. [Diásporas chinas a las Américas] - Chang-Rodríguez, Eugenio (新世界出版社[New World Press], 2021)
Keywords: dept.wll

儿童与战争: 童年回忆和西班牙内战研究 = Children and the war - Weng, Miaowei (中国社会科学出版社, 2020)
本书将儿童,童年回忆和西班牙内战联系在一起,提出了"佛朗哥儿童"这个新概念.在童年研究和历史回忆研究的二元框架下,作者分析了"佛朗哥儿童"在西班牙20世纪后半叶至今的代表性文学影视作品,以此揭示出儿童在西班牙政治中的重要性,并呈现了西班牙近几十年来的历史和文化走向
Keywords: Wen xue yan jiu Xibanya; dept.wll

Coping with a language loss: A case of linguistic and cultural re-encoding of memories in language attriters - Sorokina, Anastasia (International Journal of Bilingualism, 2023)
Aims and objectives:This study investigates the effects of language loss on bilingual autobiographical memory. More specifically, the study focuses on whether severe language loss would lead to any linguistic changes and/or interfere with how memories are recalled and shared.Methodology:Autobiographical memories were elicited with the help of a cued-recall technique and memory questionnaire from two groups of immigrants?attriters (who experienced significant language loss) and bilinguals (who retained their first language proficiency).Data and analysis:The data set consisted of pre-immigration memories that were originally encoded in the first language, Russian. The frequency of recall (i.e., sharing memories with others as well as reminiscing) and linguistic components (i.e., words) of memories elicited from the attriters and bilinguals were analyzed quantitatively and qualitatively.Findings and conclusion:Overall, attriters were able to recall memories that were originally encoded in the forgotten language. They also reported reminiscing about their pre-immigration memories and sharing their memories with others. However, attriters revealed that the pre-immigration memories came to them with words in the second language, English, which was not the case with bilinguals. Attriters also reframed memories for several Russian culture-specific items and events. This finding is indicative of memory re-encoding?a phenomenon when memories are updated, stored, and subsequently retrieved with added information. While this finding points to the bilingual mind?s ability to adapt to language loss, it may also suggest linguistic and cultural assimilation under the influence of the new language and culture.Originality:This is the first investigation of autobiographical memory in bilinguals with severe language loss that highlights the malleability and adaptability of the bilingual mind as well as the importance of language maintenance.
Keywords: dept.wll; peer-reviewed

Food Cultures of Mexico: Recipes, Customs, and Issues - Hernández Rodríguez, Rafael (Global kitchen (Greenwood Press (Westport, Conn.)), 2021)
"This exciting volume brings to life the food culture of Mexico, detailing the development of the cuisine and providing practical information about ingredients and cooking techniques so that readers can replicate some of Mexico's most important traditional dishes"--
Keywords: Cooking / Regional & Ethnic / Central American & South American; Cooking / Regional & Ethnic / Mexican; Food habits; History / Latin America / Mexico; Mexico; Cooking, Mexican; Mexico; Social life and customs; dept.wll

Developing self-directed learning strategies through creative writing: Three case studies of snowball writing practice in a college Chinese language classroom - Tu, I. Ju (Thinking Skills and Creativity, 2021)
This study investigates three learners’ self-directed learning (SDL) strategies in a college beginner level Chinese language classroom. Using a focus group and interviews to explore how the students recognize their own learning strengths and weaknesses, what strategies they develop during the SDL process, their awareness of learning contexts while adopting SDL, and how they exercise their agencies for SDL. Findings suggest that technology fluency, the disconnection between learning goals and SDL strategies, and learners’ unawareness of their learning strengths affects individuals’ agency regarding SDL strategies. These findings suggest the need for further discussion of language teachers’ role in instructing SDL strategies, the role of technology, and the use of written corrective feedback. © 2021
Keywords: dept.wll; peer-reviewed

Readings of “Hum dekhenge” by faiz ahmed faiz. Islamic images, revolution, or anti-Hindu sentiments? - Meagher, G.C. (Estudios de Asia y Africa, 2021)
This article examines the controversy caused by the Faiz Ahmed Faiz’s poem “Hum Dekhenge” during the protests triggered by the approval of the Citizenship Amendment Act and the National Registry of Citizens at the end of 2019 in India. In addition to a Spanish translation of the actual text, it also offers a background of the debate, a biographical sketch of the poem’s author, and diverse interpretations. The production of meaning is a complex articulation between text, readers, and the sociopolitical context. “Hum Dekhenge” is a poem of various linguistic, literary, and political registers. Without question its reading is open to multiple possibilities. © 2021. Estudios de Asia y África.
Keywords: dept.wll

Dark Ecology in One Hundred Years of Solitude and Love in the Time of Cholera (Chapter 20) - Flores, William (The Oxford Handbook of Gabriel García Márquez, 2021)
From the epic saga of the Buendía family in One Hundred Years of Solitude to the enduring passion of Love in the Time of Cholera to the exploration of tyranny in The Autumn of the Patriarch, Gabriel García Márquez has built a literary world that continues to captivate millions of readers across the world. His writings entrance modern audiences with their dreamlike yet trenchant insights into universal issues of the human condition such as love, revenge, old age, death, fate, power, and justice. A Nobel Laureate in 1982, he contributed to the global popularity of the Latin American Boom during the second half of the 20th century and had a profound impact on writers worldwide, including Toni Morrison, Salman Rushdie, and Haruki Murakami. The Oxford Handbook of Gabriel García Márquez brings together world experts on the Colombian writer to present a comprehensive English-language examination of his life, oeuvre, and legacy--the first such work since his death in 2014. Edited by Latin American literature authorities Gene H. Bell-Villada and Ignacio López-Calvo, the volume paints a rich and nuanced portrait of "Gabo." It incorporates ongoing critical approaches such as feminism, ecocriticism, Marxism, and ethnic studies, while elucidating key aspects of his work, such as his Caribbean-Colombian background; his use of magical realism, myth, and folklore; and his left-wing political views. Thirty-two wide-ranging chapters cover the bulk of the author's writings-both major and minor, early and late, long and short-as well as his involvement with film. They also discuss his unique prose style, highlighting how music shaped his literary art. The Handbook gives unprecedented attention to the global influence of García Márquez-on established canons, on the Global South, on imaginative writing in South Asia, China, Japan, and throughout Africa and the Arab world. This is the first book that places the Colombian writer within that wider context, celebrating his importance both as a Latin American author and as a global phenomenon.
Keywords: dept.wll

Cine Politico en Mexico (1968-2017) - Hernandez Rodriguez, Rafael (Latin Americanist, 2020)
Keywords: dept.wll; peer-reviewed; ⛔ No DOI found

Empirical insights into college students’ academic reading comprehension in the united states - Kalbfleisch, Elizabeth; Schmitt, Elena; Zipoli, Richard P. (Journal of College Reading and Learning, 2021)
This article reports on a collaborative research project involving faculty in writing studies, communication disorders, and applied linguistics that sought to empirically describe the reading skills of students (N = 910) in freshman composition classes at one college and two universities in the northeast United States. The research team developed and administered a questionnaire that evaluated students’ reading abilities according to six categories: inferential ability, background knowledge, general comprehension, vocabulary, figurative language/jargon, and morphosyntactic structures (grammar/syntax). Our statistically significant results showed that students scored best in the categories of background knowledge and general comprehension, which are well researched in a college population. However, students struggled in categories such as figurative language/jargon and morpho-syntactic structures, which are not well researched in a college population. Further, comprehension seemed generally discrete (understanding specific points of an essay) rather than holistic (indicated by an ability synthesize those points into a general statement about the author’s thesis). These findings suggest that further empirical research in this area will help describe the reading skills of college students and consequently will inform the development of pedagogical approaches that more effectively address students’ current needs. © 2021 College Reading and Learning Association.
Keywords: dept.cmd; dept.eng; dept.wll; peer-reviewed

Redemptive children and historical memory: Luis mateo díez’s la gloria de los niños (2007) - Weng, Miaowei (Bulletin of Spanish Studies, 2020)
This article explores contemporary Spanish writer Luis Mateo Díez’s 2007 novel, La gloria de los niños, focusing on the construction of a redemptive child who mends the broken world and keeps alive historical memory. The author looks beyond one single nation state in his reconstruction of children and childhood under the Franco regime. Hidden behind his approach to the reconstruction of the ‘glorious children’ under Franco emerges, on the one hand, his dissolution of any authoritative version of Franco-era children and, on the other, his broader vision and desire to examine Spain and Spanish historical memory in a global context. © 2020 Bulletin of Spanish Studies.
Keywords: Childhood under Franco; Historical Memory; La gloria de los niños; Ladri di biciclette (1948); Luis Mateo Díez; Post Civil War period; Redemptive Child; Vittorio de Sica; Walter Benjamin; dept.wll; peer-reviewed

The knowledge framework for building teacher awareness of language in content instruction - Gleason, Jesse; Schmitt, Elena (Social practices in higher education - A knowledge framework approach to linguistic research and teaching, 2021)
Keywords: dept.wll; faculty_collection